DEFAULT AND FRAGILITY IN THE PAYMENT SYSTEM - Paula Lourdes Hernandez Verme (European Scientific Journal, ESJ, 2013)
I present a model of the payment system where agents may choose whether or not to default on debt. Our model also features debt-financed purchases of goods, unsecured debt cleared through third parties, and debt settlement requiring final payment using fiat money. I compare the merits of three alternative settlement rules: a strict net settlement rule, a net settlement rule with debt forgiveness and a gross settlement rule. I find that net settlement is superior to gross settlement and that only a net settlement rule with debt forgiveness gives the correct incentives for a unique, stable and optimal stationary equilibrium.